TiO2 decorated sand grains for photodegradation of pollutants: Methylene blue and ciprofloxacin study - Lacerda, Jorge A.S.; Macedo, Allan M.; Teixeira, Rodolfo I.; Simões, Grazieli; Ribeiro, Emerson S. [UNESP]; Forero, Josué S.B.; Corrêa, Rodrigo J. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2020)
This study shows a preparation and evaluation of a new non-expensive TiO2 based photocatalyst built over sand grains surfaces as an alternative green technology for water treatment. The semiconductor covalently bonded to the silica sand grains (sand@TiO2) prepared by hydrolysis of isopropoxide orthotitane over sand grains, showed a high surface area 296 m2 g-1 and a high reaction rate for methylene blue (MB) photodegradation (0.064 min-1), on steady state condition by using 3 g of sand@TiO2 and an MB solution (20 mL, 3 × 10-5 mol L-1) or ciprofloxacin hydrochloride (CIP) solution (20 mL, 1.9 × 10-3 mol L-1). Under UV irradiation with a medium pressure Hg lamp, the total MB removal reached 70% after 7 min and 45% for CIP in 60 min. Further, the photocatalyst showed to be a promising reusable material for removal of ciprofloxacin hydrochloride antibiotic (CIP) on wastewater. This new material appears as a new promising low cost and low impact reusable catalyst for water treatment.
Keywords: Ciprofloxacin; Methylene blue; Photodegradation; Reusable catalyst; TiO2